Assessment of dietary habits among Polish women with Hashimoto’s disease (Journal of Medical Science, 2023)
Introduction. Selected dietary components are crucial for a properly functioning thyroid gland. Therefore a healthy and balanced diet is crucial for treating patients with Hashimoto’s disease. Aim. This study aims to evaluate the dietary habits of women suffering from autoimmune thyroiditis. Material and methods. A questionnaire study was conducted in a group of 58 women with Hashimoto’s disease and among 42 women without autoimmune thyroiditis using the Food Frequency Questionnaire (FFQ-6). To assess compliance with the normal distribution, we used the Shapiro-Wilk test. The comparative assessment was made using the Student’s t-test and Mann-Whitney test. The Chi-square test was used to assess the relationship between the response and the group. A p-value of less than 0.05 was considered significant. Results. The study showed no significant differences in dietary habits between the two groups. Only 29% (n=15) of women with HT declared daily consumption of fruits vs 31% (n=12) in the control group (p=0.3800), and only 2% (n=1) declared consuming berries daily vs. 5% (n=2), (p=0.5270). The consumption of the recommended several portions of vegetables per day was declared by only 22% (n=11) of women with HT vs 28% (n=11) in the control group (p=0.3983). 42% (n=24) of women with HT vs 38.5% (n=16) of controls reported eating cruciferous vegetables several times a week (p=0.8241). 14% (n=8) of women with HT vs 19% (n=8) of women in the control group declared daily consumption of green leafy vegetables (p=0.3653). Most people in the study group consume nuts and seeds several times a month, and those in the control group several times a week. Most HT respondents also declare not to consume the recommended amount of fish. Conclusions. The diet of patients with Hashimoto’s disease does not differ significantly from that of non-Hashimoto’s disease patients. Considering the study results and current scientific knowledge, it seems necessary to undertake educational activities for patients with Hashimoto’s disease to increase patient awareness of the impact of diet on the course of the disease.